2019
DOI: 10.1093/jcag/gwz002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association Between Referral Quality, Wait Time and Patient Outcomes for Patients Referred to an IBD Specialty Program

Abstract: Abstract Background Most speciality inflammatory bowel disease (IBD) care can only be accessed through a referral. Timely access to specialty care has been associated with improved disease-related outcomes. To receive appropriate care, the referral needs to include high-quality information. To date, no research has explored the association between referral quality and IBD patient outcomes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…8,18 Our audit did not explore factors contributing to delays, but did reveal that over half of referrals were inadequate in terms of temporal and disease stratification. The inconsistency of referral quality is substantiated in the literature 16 and may contribute to delays with prioritisation and triage. Strategies aimed at improving the delivery of care and improved patient outcomes have been discussed in the literature such as referral initiatives, resource alignment, operational efficiency and process improvement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,18 Our audit did not explore factors contributing to delays, but did reveal that over half of referrals were inadequate in terms of temporal and disease stratification. The inconsistency of referral quality is substantiated in the literature 16 and may contribute to delays with prioritisation and triage. Strategies aimed at improving the delivery of care and improved patient outcomes have been discussed in the literature such as referral initiatives, resource alignment, operational efficiency and process improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For enuresis, detailed information could help redirect the patient to a more appropriate clinic and decrease wait time to treatment. The importance of timely care is supported by a Canadian study that revealed increasing waiting times were associated with disease flares, hospitalisations and additional referrals for patients with inflammatory bowel disease 16 . They also highlighted the shortfalls of referrals, where 20% of referrals did not include the diagnosis, 45% did not report the duration and 29% did not report severity 16 .…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Additionally, patients who are referred with incomplete referrals can experience longer wait times than those referred with more complete referrals as they may be perceived as less urgent. 25 Lengthy wait lists can also cause the content of interminably queued referrals to become outdated. 6 Referral quality may differ depending on the referrer’s profession 8 and referral format, 26 and standardised referral templates can mitigate such issues.…”
Section: Introductionmentioning
confidence: 99%